Effect of Mg, Si and Cu content on the microstructure of dilute 6000 series aluminium alloys - Aiza, Jaafar; Azmi, Rahmat, Prof. Madya Dr.; Zuhailawati, Hussain, Prof. Madya Dr.; Ismail, Zainol, Prof. Madya Dr. (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/